3' editing of mRNAs: sequence requirements and involvement of a 60-nucleotide RNA in maturation of histone mRNA precursors. - Birchmeier, C (1984)
In vitro-synthesized transcripts of the sea urchin histone H2A gene with 3' extensions are efficiently and rapidly processed to H2A mRNA with faithful 3' ends in Xenopus laevis oocyte nuclei. Processing requires the presence of a histone-specific dyad symmetry element and of H2A-proximal spacer sequences in the precursor RNA. In DNA injection experiments with a processing-deficient H2A mutant, the transcription products appear to terminate heterogeneously in the first 100-200 base pairs of the post-H2A spacer. Processing of synthetic H3 RNA precursors requires the prior injection of a 60-nucleotide RNA from sea urchin embryos that seems to be a component of a small nuclear ribonucleoprotein.